The King's English - Fowler, H. W (Oxford University Press, 1973)
A Parthian shot from one of the most important figures in post-war British fiction, The King's English is the late Kingsley Amis's last word on the state of the language. More frolicsome than Fowler's Modern Usage, lighter than the Oxford English Dictionary, and brimming with the strong opinions and razor-sharp wit that made Amis so popular--and so controversial--The King's English is a must for fans and language purists.